A DNA vaccine encoding the viral hemorrhagic septicemia virus genotype IVb glycoprotein confers protection in muskellunge (Esox masquinongy), rainbow trout (Oncorhynchus mykiss), brown trout (Salmo trutta), and lake trout (Salvelinus namaycush). Issue 1 (December 2016) - Standish, Isaac; Millard, Elena; Brenden, Travis; Faisal, Mohamed
Abstract Background The viral hemorrhagic septicemia virus (VHSV) is one of the most serious fish pathogens. In 2003, a novel sublineage (genotype IVb) of this deadly virus emerged in the Great Lakes basin causing serious fish kills. We have previously demonstrated that a DNA plasmid (pcDNA), containing a cytomegalovirus (CMV) promoter and the viral hemorrhagic septicemia virus (VHSV) genotype IVb glycoprotein (G) gene insert (designated pVHSivb-G) confers moderate protection in muskellunge (Esox masquinongy ), a highly susceptible species upon challenge. In order to achieve optimal protection, we investigated a number of factors including the incubation time [i.e. the number of degree days (° days)] before challenge, and viral challenge dose and route. Additionally, we tested if pVHSivb-G provides protection against VHSV-IVb to less susceptible salmonids such as rainbow trout (Oncorhynchus mykiss ), brown trout (Salmo trutta ) and lake trout (Salvelinus namaycush ). Results An increase in the period lapsed between vaccination and challenge to 1880° days resulted in 95% relative percent protection (RPS) in muskellunge following a single administration of the pVHSivb-G plasmid and viral challenge. An RPS of 100% for muskellunge was achieved with a longer incubation period (2400° days) and in conjunction with a booster dose of the plasmid. The pVHSivb-G vaccine also elicited significant protection in all three salmonid species, reaching 100% RPS in lake trout following an incubation period of 1001° days prior to viral challenge. Vaccination with pVHSivb-G was also associated with the development of significant levels of circulating VHSV-binding antibodies in muskellunge as measured by indirect ELISA, which reached peak levels 6–7 weeks post-vaccination. Viral shedding in vaccinated survivors was minimal and of transient nature. Conclusions The study shows that the pVHSivb-G plasmid can elicit a protective response against the wild virus strain in a range of species important in recreational and commercial Great Lakes fisheries.